Feedback : Old and new quantum. (21st July 2016) - Forbes, Richard
Abstract: In reply to the physicsworld.com news article "'Quantum manifesto' for Europe calls for €1bn in funding" (17 March, http://ow.ly/ZCAa9) about a proposed EU fund for quantum technologies.